Phytochemical Screening and Antioxidan Activity of Several Types of Mango Seeds - Nurmala Sari; Sujarwati Sujarwati (Biology Education Study Program, Faculty of Teacher Training and Education, University of Mataram, Indonesia, 2023)
Mango is one type of fruit that is most popular with the public. The use of mangoes is only for the flesh for consumption, while the skin and seeds are discarded, causing organic waste in the environment. This study aims to determine the content of secondary metabolites and antioxidant activity in the seeds of arum manis mango (Mangifera indica Linn.), kweni mango (Mangifera odorata Griff.) and bacang mango (Mangifera foetida Lour.). Mango seed extract was made by maceration method using 70% methanol solvent. The phytochemical test was carried out qualitatively and the antioxidant activity test was carried out using the DPPH (2,2-diphenyl-1- picrihidrazyl) method. The results of the phytochemical tests showed that the methanol extracts from the seeds of arum manis, kweni and bacang mangoes contained the same secondary metabolites, namely alkaloids, flavonoids, triterpenoids, tannins and saponins. Bacang mango seeds have a higher content of secondary metabolites compared to arum manis and kweni mango seeds. Antioxidant activity test showed that the methanol extract of arummanis, kweni and bacang mango seeds had an IC value below 50 which was classified as very strong antioxidant activity. Of the three samples, arum manis mango seed extract had the strongest antioxidant activity (2.84 µg/mL) compared to bacang mango seeds (2.85 µg/mL) and kweni (3.22 µg/mL).